Performance Assesment Based on Malcolm Baldrige Model Criteria in The Automotive Industry: A Case Study - Silitonga, Riana Magdalena; Jou, Yung-Tsan (Metris: Jurnal Sains dan Teknologi, 2021)
The performance of a company is supported by the performance of workers from various departments and levels of work in the company. Performance measurement is needed to evaluate the condition of the company. Bakom Metal Industry is an automotive company that produces pistons. BMI is an OEM company that has become a supplier to several large companies such as Astra and Daihatsu. One of the departments that play an essential role in increasing the company's sales is the Production Department. Therefore, this study aims to assess the current performance of the production department and provide improvement strategies to achieve performance excellence and quality using the Malcolm Baldrige method. The assessment in this study uses two methods, qualitative and quantitative methods. The evaluation result based on the interview got a value of 618.5, and based on the questionnaire got a weight of 734.79. Based on the outcome of the two methods, it indicates that the production department has shown good performance, which is included in the excellent category as an industry leader. The assessment in the production department will provide the strengths and opportunities for evaluation to improve the performance and to be able to compete with competitors.